Preaching and leading worship - Willimon, William H. (The Pastor's handbooks, 1984)
The central task of the Christian community--worship--is the focus of this thought-provoking book. William H. Willimon moves from theological understanding to the practical skills needed for preaching and worship leadership. He sets standards for evaluating a good service and then tells how to plan one. He offers useful guidelines for conducting public prayer and for celebrating the Lord's Supper and Baptism. Focusing on preaching, he describes how to construct a sermon, deliver it convincingly, and evaluate it. He concludes with valuable suggestions for involving the laity in worship.